Cover Picture: Photoelectrochemical Reduction of Carbon Dioxide to Methanol through a Highly Efficient Enzyme Cascade (Angew. Chem. Int. Ed. 14/2017). Issue 14 (17th February 2017) - Kuk, Su Keun; Singh, Raushan K; Nam, Dong Heon; Singh, Ranjitha; Lee, Jung‐Kul; Park, Chan Beum
Abstract : An artificial photosynthetic platform … … has been created by combining a photoelectrochemical cell and a multienzyme cascade to mimic natural photosynthesis in green plants. J. K. Lee, C. B. Park, and co‐workers describe in their Communication onpage 3827 ff. how the use of water as an electron donor, a hematite photoanode, and a bismuth ferrite photocathode for the regeneration of NADH with visible light, as well as a three‐dehydrogenase cascade system allows the highly selective and fast conversion of carbon dioxide into methanol.